“If You Can’t See It, You Can’t Be It!” News Media Engagement and Gender Differences Among Irish Economists - Doyle, Orla; Howard, Emma (The Economic and Social Review, 2024)
Women are under-represented across most facets of economics. One under-investigated area of research is their participation in the media. The absence of female representation may contribute to the perception of economics as a largely male dominated discipline, with consequences for role modelling, influencing public debate, and ultimately policy decisions. Using an online self-reported survey, this study investigates levels of news media engagement among economists in Ireland and the supply-side factors influencing barriers to engaging with the media. We find that women economists are less likely to be invited to participate in news media events compared to their male counterparts. Women are also more likely to refuse to participate and require longer to prepare for an interview. While there are no gender differences regarding feeling equipped to deal with the media, women are less confident and more likely to state that media engagement is not an important part of their working lives. Despite this, women feel a greater responsibility to inform the public about the implications of their research, and to act as role models for junior economists. Our findings suggest that a multi-faceted approach is required to achieve greater gender equality – by economists themselves, who could build media networks and promote their research through different channels; by employers, who could give women economists more time to engage with the media; by journalists, who could better foster and build relationships with women economists; and by representative bodies, who could better communicate the depth and diversity of economists’ areas of expertise.